"Rehab for all!" Is it too early in pulmonary arterial hypertension?. Issue 5 (7th November 2019) - Bertoletti, Laurent; Bouvaist, Hélène; Tromeur, Cécile; Bezzeghoud, Souad; Dauphin, Claire; Enache, Irina; Bourdin, Arnaud; Seronde, Marie-France; Montani, David; Turquier, Ségolène; Pison, Christophe
Chronic pulmonary hypertension shares abnormalities found in chronic left heart failure and chronic respiratory failure, in which rehabilitation has been proposed [1, 2]. In a recent statement endorsed by the European Respiratory Society, Grünig et al. [3] proposed an exhaustive review of available data on rehabilitation in the setting of chronic pulmonary hypertension. The main messages proposed are "Specialised exercise training in patients with pulmonary hypertension appears to be effective, cost-efficient and safe." Rehabilitation appears to be beneficial in PAH patients, but more research is needed before increasing the level of evidence for recommendations. http://bit.ly/33zutuZ